Sugerencias para Escribir un Buen Artículo Científico en Educación - F. Javier Murillo; Cynthia Martínez-Garrido; Guillermina Belavi (Universidad Autónoma de Madrid, 2017)
What are the characteristics of good articles of educational research? In this paper, we provide some useful suggestions for writing articles that can be published in academic journals with high impact. This collection of ideas emerges from three different sources: our experience as authors and editors of educational research journals, the review of other texts with similar objectives published in fields rather than education, and they come from the results of an exploratory study of 20 exemplary quantitative and qualitative' research papers (10 published in the most prestigious Spanish academic journals in the field of Educational Research, the other 10 have been published in the international journals with the higher impact factor). Throughout the article, it appears recommendations and examples that include: steps to elaborate a research article, how to structure the paper in sections, recommendations about the writing style of all the single sections of the paper considering the quantitative and qualitative kind of paper, and different aspect to consider in order to find the target journal to submit the paper.